A computational study of the electronic structure and optical properties of the complex TeO2/TeO3 oxides as advanced materials for nonlinear optics. (20th November 2019) - Roginskii, E M; Smirnov, M B; Kuznetsov, V G; Noguera, O; Cornette, J; Masson, O; Thomas, P
Abstract: Electronic structure of series of tellurium oxide crystals within the TeO2 —TeO3 binary system is studied with generalized gradient approximation to DFT, hybrid DFT-HF method with the PBE0 and B3LYP exchange-correlation functionals and with quasiparticle G 0 W 0 approach. Comparison with available experimental data revealed significant underestimation of the band gap values within DFT. The hybrid DFT-HF method leads to slightly overestimated values of the bandgap, and the best agreement with experimental data provides the 'one-shot' G 0 W 0 calculations starting from Kohn–Sham solutions. The electronic structure of tellurium oxides is discussed in details. It is found that the bandgap value decreases proportionally to fraction of tellurium atoms in octahedral coordination. This change is due to formation of gap states by 5s(Te) electrons which do not participate in Te(VI)–O bonding. Dielectric susceptibilities are calculated within Random Phase approximation for the series of tellurium oxides and high nonlinear properties of the compounds are predicted by empirical Miller's rule.